Happiness and unemployment: the case of Malaysian graduates / Hock-Eam Lim - Lim, Hock-Eam (2008)
The objective of this paper is to study the determinants of graduates' happiness during their transition from university to labour market, with the focus on the effect of their employment status. Results of descriptive statistics reveal that there is a decreasing trend of happiness over the duration of unemployment. In particular, the happiness level drops from 'happy' to 'unhappy' after 90 days of being unemployed. Estimated Ordered Logit model shows that there is a negative psychological impact of unemployment. This negative impact is intensified after 180 days of being unemployed. Specifically, compared to those unemployed, those employed with full-time employment that commensurate with qualification are found to be happier. Other significant determinants of graduates' life happiness are financial difficulties, religions, types of degree and age.